Upregulated Expression of VLA Proteins and CD29 in Peripheral Blood Lymphocytes of Chronic Alcoholics Without Ethanol-Related Diseases - Sacanella, E.; Estruch, R.; Gaya, A.; Ferrer, K.; Fernández-Sola, J.; Alonso, J. R.; Nicolás, J.M.; Urbano-Márquez, A. (Alcoholism, clinical and experimental research, 1999)
To analyze adhesion molecule expression on peripheral blood mononuclear cells (PBMCs) and on different lymphocyte subpopulations (CD2+, CD8+, CD19+, and CD56+ subsets) in chronic alcoholism, 30 well‐nourished chronic alcoholics without ethanol‐related diseases and 30 matched controls were included in the study. Adhesion molecules that mediate adhesion to other cells and to extracellular matrix proteins, and whose cellular expression is modified during lymphocyte activation, were selected for study. A detailed clinical evaluation, laboratory analysis, nutritional assessment, and study of adhesion molecule expression was performed. A significant higher expression of CD29 (β1‐integrin) (p= 0.001), VIA‐3 (p= 0.002), VLA‐4 (p= 0.03), and VLA‐5 (p= 0.001) were observed on PBMCs of chronic alcoholics, compared with control subjects, whereas no changes were observed in CD18 (β2‐integrin) and CD50 (ICAM‐3) expression. The upregulation of CD29 and VLA proteins only affected T lymphocytes (CD2+/CD8+/CD4+ cells). These data confirm that T cells of chronic alcoholics are basally activated and that changes in adhesion molecule expression on PBMCs may be responsible of disturbances of adhesion processes in chronic alcoholics without ethanol‐related diseases.